2012
DOI: 10.1177/0748233712457439
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of lutein against benzo(a)pyrene-induced oxidative stress in human erythrocytes

Abstract: The present study was carried out to evaluate the in vitro antioxidant properties and protective effect of lutein in human erythrocyte against benzo(a)pyrene (B(a)P). It is a well-known environmental carcinogen that produces free radicals under normal metabolic circumstances. B(a)P reacts with cellular macromolecules and produces oxidation of protein, lipid and DNA. Lutein is a carotenoid possessing antioxidant, anticarcinogenic and anti-inflammatory properties. In the present investigation, the protective eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 51 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…Indeed, this compound strongly suppressed the expression of MMP-9 (Figure 2(c)), a marker of acute inflammation [44], implying that lutein is capable of modulating UV-mediated inflammatory and cellular damage by suppressing radical generation. In addition, lutein has been reported to reduce oxidative stress induced by benzo(a)pyrene [45], hypercholesterolemic diet [46], H 2 O 2 [47], and D-galactose [48]. Taken together, these prior reports and our new data suggest that the radical scavenging activity of lutein is a common feature observed in lutein pharmacology.…”
Section: Resultssupporting
confidence: 81%
“…Indeed, this compound strongly suppressed the expression of MMP-9 (Figure 2(c)), a marker of acute inflammation [44], implying that lutein is capable of modulating UV-mediated inflammatory and cellular damage by suppressing radical generation. In addition, lutein has been reported to reduce oxidative stress induced by benzo(a)pyrene [45], hypercholesterolemic diet [46], H 2 O 2 [47], and D-galactose [48]. Taken together, these prior reports and our new data suggest that the radical scavenging activity of lutein is a common feature observed in lutein pharmacology.…”
Section: Resultssupporting
confidence: 81%
“…Lutein (~30 μM) significantly decreases several skin inflammatory responses, such as the increased expression of IL‐6 from LPS‐treated macrophages, up‐regulation of COX‐2 from IFN‐𝛾/TNF‐𝛼‐treated aneuploid immortal keratinocyte cells (HaCaT cells) and the enhancement of MMP‐9 levels (a marker of acute inflammation) in UV‐irradiated keratinocytes (Oh et al ., ). Lutein acts as a strong antioxidant; it reduces oxidative stress induced by benzo(a)pyrene (Vijayapadma et al ., ), a hypercholestrolaemic diet (Kim et al ., ), H 2 O 2 (Gao et al ., ) and D‐galactose (Mai et al ., ). Lutein supplements (~20 mg·day −1 ) resulted in a significant decrease in serum IL‐6 and monocyte chemoattractant protein‐1 (MCP‐1), triglyceride (TG) and LDL in early atherosclerosis for 3 months (Xu et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies have shown an inverse relationship between the intake of lutein and the presence of age-related macular degeneration (Mares-Perlman et al, 2001), cataracts (Olmedilla et al, 2003;Gale et al, 2014;Liu et al, 2014) and retinitis pigmentosa (Beatty et al, 2000). Lutein antioxidant activity has been biochemically reported in in vitro studies using human erythrocytes (Vijayapadma et al, 2014) and human retinal pigment epithelial cells . Studies on the effects of lutein in oxidative stress parameters in lab animals and cell cultures have shown that lutein might act as a scavenger and also inducing the expression of genes related to a better antioxidant response (Serpeloni et al, 2014;Aimjongjun et al, 2013) There are several similarities between the inner ear and the retina.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of literature is necessary to further analyse these findings, but it is remarkable how often antioxidant molecules have been tested as potential otoprotectors. Lutein is a carotenoid with antioxidant, anticarcinogenic and antiinflammatory properties (Vijayapadma et al, 2014). In the field of ophthalmological diseases, it is well known that lutein and zeaxanthin are present in the macula and lens of the human eye (Landrum and Bone, 2001;Olmedilla-Alonso et al, 2014).…”
Section: Discussionmentioning
confidence: 99%